Pilot Randomised, Double‐Blind, Placebo‐Controlled Crossover Trial Evaluating the Feasibility of an Intranasal Oxytocin in Improving Social Cognition in Individuals Living with Alzheimer's Disease. (20th December 2022) - Michaelian, Johannes C; McCade, Donna; Hoyos, Camilla M; Brodaty, Henry; Harrison, Fleur; Henry, Julie D; Guastella, Adam J; Naismith, Sharon L
Abstract: Background: Individuals living with Alzheimer's disease (AD) demonstrate global deficits in social cognition. These deficits have been associated with impaired interpersonal relationships amongst caregivers, in turn contributing to a greater sense of caregiver 'burden'. In other areas of neuropsychiatric disease (i.e., autism spectrum disorder), intranasal oxytocin (INOT) administration has shown replicable improvements in social cognitive function, particularly in Theory of Mind. Recently, randomised controlled trials (RCTs) in frontotemporal dementia have reported that repeated INOT administration may be regarded as safe and well tolerated at higher doses ‐ resulting in changes to apathy and improvements in empathic concern, as rated by a caregiver. To date, no studies have investigated the feasibility of an INOT treatment in individuals living with AD. Here, we conducted a pilot feasibility trial to determine the feasibility of recruitment, the acceptability of enrolment and the adherence to an INOT treatment in order to inform the subsequent design of a future RCT. Secondly, we sought to determine the effect size estimates on key potential social cognitive function outcome measures related to both the participant and their caregiver. Method: Four individuals living with AD were enrolled in a single‐centre, randomised, double‐blind, placebo‐controlled crossover trial involving a one‐week treatment period with both INOT (72 IU) and placebo. Result: All participants reported no treatment‐causative or serious adverse events, following repeated INOT administration. While acceptability of enrolment was excellent (100%), as well as INOT treatment adherence (placebo, 95%; INOT, 98%), our feasibility of recruitment was not acceptable (i.e., only 7% of fifty‐eight individuals with dementia screened met inclusion criteria). However, positive/large effects were associated with expected secondary outcomes around self‐reported health and wellbeing, caregiver 'burden', intimacy and interpersonal bonding, following repeated INOT administration. Conclusion: These data provide the first evidence demonstrating the safety and tolerability of INOT administration in individuals living with AD. Despite limitations in sample size, moderate‐to‐large effect size improvements were identified in participant health outcomes as well as core social cognitive functions and burden as reported by a caregiver. This suggests potential broad‐ranging beneficial effects of INOT which should be assessed in future RCTs from multiple perspectives.